2012
DOI: 10.1111/j.1462-5822.2012.01827.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel role of ESAT-6-dependent miR-155 induction during infection of macrophages withMycobacterium tuberculosis

Abstract: SummaryMycobacterium tuberculosis (M.tb.) replicates in host macrophages to cause tuberculosis. We have investigated the role of miRNAs in M.tb.-infected murine RAW264.7 cells and bone marrow-derived macrophages (BMDMs), focusing on miR-155, the most highly upregulated miRNA. We observed that miR-155 upregulation is directly linked to the attenuation of expression of BTB and CNC homology 1 (Bach1) and SH2-containing inositol 5Ј-phosphatase (SHIP1). Bach1 is a transcriptional repressor of haem oxygenase-1 (HO-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 54 publications
2
123
0
1
Order By: Relevance
“…However, with some exceptions (17,(30)(31)(32)(33)(34)(35), the majority of these studies have failed to identify downstream effects on the host immune response for the miRNAs detected with altered expression. A major contributing factor to the lack of concrete targets is the use of mixed cell populations or sputum for the identification of differentially expressed miRNAs during M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, with some exceptions (17,(30)(31)(32)(33)(34)(35), the majority of these studies have failed to identify downstream effects on the host immune response for the miRNAs detected with altered expression. A major contributing factor to the lack of concrete targets is the use of mixed cell populations or sputum for the identification of differentially expressed miRNAs during M. tuberculosis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-155 expression is increased by a wide variety of stimuli, such as TLR ligands (16), and has been shown to promote both antimicrobial (17) and antiviral responses of macrophages (18) through the repression of factors antagonistic to the inflammatory response. For example, by repressing the transcripts encoding suppressor of cytokine signaling 1 and Src homology 2 domain-containing inositol 5-phosphatase 1, mir-155 promotes immunity to Staphylococcus aureus (19) and Francisella tularensis (20), respectively, but negatively impacts Mycobacterium tuberculosis infection (21). Mir-155 has also been reported to be integral in the development of IL-17A-producing CD4 ϩ T cells (Th17 cells) (22), mainly in the context of autoimmune inflammation (16,23), but also during gastrointestinal infection with Helicobacter pylori (24).…”
mentioning
confidence: 99%
“…We also found that miR-125a expression in BMDMs was increased by stimulation with ESAT-6 or an avirulent (H37Ra) M. tuberculosis strain (data not shown). Recent study showed that miR-155 is highly upregulated in RAW264.7 cells and BMDMs in response to M. tuberculosis infection and ESAT-6 stimulation, and it plays a role in the downregulation of BTB and CNC homology 1 and SHIP1 to modulate host innate immune responses (44). Additionally, another study reported that miR-99b is highly upregulated in M. tuberculosis H37Rv-infected dendritic cells and macrophages, and it contributes to the enhancement of intracellular bacterial growth and downregulation of proinflammatory cytokines (45).…”
Section: Discussionmentioning
confidence: 99%